2002
DOI: 10.1007/s10038-002-8652-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel missense mutations in the human lysosomal sialidase gene in sialidosis patients and prediction of structural alterations of mutant enzymes

Abstract: Three novel missense mutations in the human lysosomal sialidase gene causing amino acid substitutions (P80L, W240R, and P316S) in the coding region were identified in two Japanese sialidosis patients. One patient with a severe, congenital form of type 2 sialidosis was a compound heterozygote for 239C-to-T (P80L) and 718T-to-C (W240R). The other patient with a mild juvenile-onset phenotype (type 1) was a homozygote for the base substitution of 946C-to-T (P316S). None of these mutant cDNA products showed enzymat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…The c.239C>T (p.P80L) mutation has been previously reported in a Japanese patient with severe congenital sialidosis type II (12). The P80 residue is situated in a conserved FRIP motif that is located at the N-terminus of the first strand of the first β-sheet unit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The c.239C>T (p.P80L) mutation has been previously reported in a Japanese patient with severe congenital sialidosis type II (12). The P80 residue is situated in a conserved FRIP motif that is located at the N-terminus of the first strand of the first β-sheet unit.…”
Section: Discussionmentioning
confidence: 99%
“…Although the NEU1 genes of the parents were not analyzed, the results suggested that the patient was compound heterozygous for p.P80L and p.D135N. The c.239C> T (p.P80L) mutation has been reported previously in a Japanese sialidosis type II patient (12). On the other hand, the c.403G>A (p.D135N) mutation has not been previously described (HGMD Professional 2011.3, Human Gene Mutation Database, Biobase, Beverly, MA, USA and SNPs reported in the database (dbSNP) of the National Center for Biotechnology information (NCBI) (http://www.ncbi.nlm.nih.gov/ SNP/)).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Using homology modeling, a potential effect of missense mutations on the sialidase tertiary structure was estimated and was correlated with the residual activity, folding, and intracellular localization of the enzyme, as well as with the clinical phenotype [Bonten et al, 2000;Lukong et al, 2000Lukong et al, , 2001Naganawa et al, 2000;Itoh et al, 2002]. For example, Lukong et al [2000] built the structural model of human sialidase using the atomic coordinates of homologous sialidases from Micromonospora viridifaciens, Salmonella typhimurium, and Vibrio cholerae.…”
Section: Missense Mutationsmentioning
confidence: 99%
“…Sialidosis type II patients are classified as those having the infantile-onset form who are relatively normal at birth, and those having the congenital-onset form that manifests prenatally and is associated with ascites and hydrops fetalis [Aylsworth et al, 1980;Beck et al, 1984]. Some authors have also used the term ''juvenile sialidosis'' to describe a form that manifests in late childhood, with a relatively mild clinical phenotype [Itoh et al, 2002;Bonten et al, 2000].…”
Section: Introductionmentioning
confidence: 99%